PENGEMBANGAN GEDUNG MEDIK RUMAH SAKIT KATHOLIK VINCENTIUS A PAULO DI SURABAYA DENGAN PENERAPAN ARSITEKTUR KONTEKSTUAL - Azka Pintra; M.D.E Purnomo; Fauzan Ali Ikhsan (ARSITEKTURA, 2015)
The design of the development of medical buildings Hospital Vincent de Paul Catholic background by importance for human health, especially in the city of Surabaya, which is one of the major cities in Indonesia, Catholic Hospital Vincent de Paul is a heritage building located in the city of Surabaya, improving services and facilities hospital class B in accordance with the standards of the Ministry of Health, Republic of Indonesia, Contextual Architecture implementation strategy to address the design. Design problem is: how to develop the design of the building of the Catholic Medical Hospital Vincent de Paul in Surabaya using Contextual Architecture implementation. The method used is a method of applying a contextual architectural design in the shape and appearance of the building. Analysis obtained an additional spaces in accordance with regulatory standards Ministry of Health of the Republic of Indonesia Hospitals class B. The spaces are not contained in the Catholic Hospital Vincent de Paul will be developed in the new medical building. The new medical building designed is a lack of facilities and services at the Hospital of the Catholic Vincent de Paul. Application of elements - elements such as materials, colors and textures on the new medical building will create a sense of harmony of a building. Repetition rhythm applied to the columns of the building will give the impression of harmony. Development of new medical building located in the city of Surabaya is expected to produce a design that context with the old buildings and the surrounding environment without leaving aspects of harmony. Keywords: Redesign of Catholic Hospital Vincent de Paul, Heritage, harmonious, Architecture Contextual